First isochronous mass measurements with two time-of-flight detectors at CSRe. (26th November 2015) - Xing, Y M; Wang, M; Zhang, Y H; Shuai, P; Xu, X; Chen, R J; Yan, X L; Tu, X L; Zhang, W; Fu, C Y; Xu, H S; Litvinov, Yu A; et al.
Abstract: Isochronous mass spectrometry (IMS) established in heavy-ion storage rings has proven to be a powerful tool for mass measurements of short-lived nuclides. In IMS, the revolution times of stored ions should be independent of their velocity spread. However, this isochronous condition is fulfilled only in the first order and in a small range of revolution times. To correct for non-isochronicity, an additional measure of the velocity or magnetic rigidity of each stored ion is required. For this purpose two new time-of-flight (TOF) detectors were installed in one of the straight sections of the experimental cooler storage ring in Lanzhou. It is expected that the resolving power of the IMS will significantly be improved with such a double-TOF arrangement. The double-TOF system was tested in a recent experiment with the 78 Kr fragments. Some of the experimental results are presented in this contribution.